Estimating the slope of the demand function at auctions for government of Canada bonds - Bo Young Chang (Bank of Canada, 2023)
We use detailed data on the bids at auctions for Government of Canada bonds between 1999 and 2021 to gauge the yield sensitivity of these bonds to the issuance amount. We propose a new metric that captures the slope of the demand function at each auction by using the information in the multiple bids (quantity and yield) that each bidder submits. In the absence of an established theoretical framework, we estimate the slope of the aggregate demand function simply by weighing the slopes of the individual demand functions, where the weights are the maximum bids of each participant. We show that these slopes can provide insights into the relationship between the supply and yield of a government debt security.
Keywords: G12; D44; 330; Debt management; Interest rates